Do bankers sacrifice value to build empires? Managerial incentives, industry consolidation, and financial performance - Hughes, Joseph P; Lang, William W; Mester, Loretta J; Moon, Choon-Geol; Pagano, Michael S (Journal of Banking & Finance, 2003)
Bank consolidation is a global phenomenon that may enhance stakeholders’ value if managers do not sacrifice value to build empires. We find strong evidence of managerial entrenchment at US bank holding companies that have higher levels of managerial ownership, better growth opportunities, poorer financial performance, and smaller asset size. At banks without entrenched management, both asset acquisitions and sales are associated with improved performance. At banks with entrenched management, sales are related to smaller improvements while acquisitions are associated with worse performance. Consistent with scale economies, an increase in assets by internal growth is associated with better performance at most banks.